Two decades of petanque research: A bibliometric analysis of dominant physical components (2002–2023) - Pelana, Ramdan; Wenly, Ayu Purnama; Ratiyono; Sukiri (Journal Sport Area, 2025)
Background: This article provides an empirical review of studies on petanque that focuses on dominant physical factors. Research Objectives: This study employs Publish or Perish software to create a homogeneous database of scientific articles from Scopus and Google Scholar-indexed journals. Researchers choose bibliometric analysis to observe and comprehend the distribution, trends, impact, and structure of scientific literature and to discuss it using predetermined keywords. Methods: Based on the results of a search on petanque with the time parameter 2002-2023, there were 268 articles found on Google Scholar and 11 articles indexed by Scopus. The selected articles focused on the dominant physical components of petanque. Findings and Results: Apply traditional bibliometric laws and use VOSviewer for data processing. These articles highlight the exponential increase in scientific production in the two decades of sport petanque. The article summarises the high fragmentation of authors with the highest levels of scientific production, 20 years of evolution in relevant thematic topics, and their concurrent concentration in three major blocks: (i) hand-eye coordination in petanque sports, (ii) kinaesthetic perception in petanque sports, and (iii) wrist flexibility in petanque sports. This article, spanning a database from two decades, provides evidence of evolution and paves the way for researchers seeking alternative visions of the predominant physical characteristics in the sport of petanque. Conclusion: This study offers valuable information about how petanque research has changed over time, shows how research affects the main physical traits of petanque, and helps explore other areas of study related to petanque. It can be concluded that the most dominant physical components in the sport of petanque are coordination, kinaesthetic perception, and wrist flexibility.